Drivers for circular economy development: making businesses more environmentally friendly - Kurita, Antonio Eiti [UNESP]; Espuny, Maximilian [UNESP]; Campos, Thalita Laua Reis [UNESP]; Kazancoglu, Yigit; Kandsamy, Jayakrishna; Oliveira, Otavio Jose de [UNESP] (Springer, 2023)
Stakeholders have been pressuring companies to develop more environmentally friendly strategic and operational solutions. In this sense, companies are seeking alternatives that reduce the negative impacts of organizational activities, Circular Economy (CE) is one of the solutions with the greatest potential for success. Thus, the goal of this paper is to provide drivers for organizations' transition from a linear to a CE. For this reason, content analysis was used as the scientific method, for being appropriate for the interpretation of qualitative data and the identification, clustering, and systematization of themes in a given field of knowledge. In the case of this work, a set of 30 articles with information related to the implementation and development of CE were analyzed, allowing the identification of 19 key elements of CE. These key elements were then grouped and systematized into four drivers: decision-making; capacity and training; sustainable practices; and green supply chain. Scientifically, this work contributes to the improvement and increase of the block of knowledge about the CE, because the drivers can be used to advance the state of the art and as a starting point for the development of new research. In an applied way, the drivers proposed in this article provide a range of actions for managers to make their companies greener and improve their organizational performance, thus contributing environmentally and socially to the planet.
Keywords: Circular economy; Environmental management; Sustainable development; Green business; Drivers; Content analysis